2008
DOI: 10.1002/marc.200800115
|View full text |Cite
|
Sign up to set email alerts
|

“Sandglass”‐Shaped Self‐Assembly of Coil–rod–coil Triblock Copolymer Containing Rigid Aniline‐Pentamer

Abstract: The amphiphilic PEG1 500‐b‐EM AP‐b‐PEG1 500 (EM PAP) triblock copolymer of poly(ethylene glycol) (PEG) and emeraldine aniline‐pentamer (EM AP) in its concentrated solution can self‐assemble into a special shape like “sandglass”, as observed by transmission electron microscopy (TEM), field emission scanning electron microscopy (ESEM) and atomic force microscopy (AFM). This “sandglass”‐shaped assembly is composed of several “rods” aggregated in the middle, with every “rod” being about 8 µm in length and 300 nm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…Huang et al has studied a coil-rod-coil triblock copolymer of poly(ethylene glycol) (PEG) and an aniline pentamer (AP), a PEG-block-AP-block-PEG system. 21 They found that when the triblock copolymer was added directly into an aqueous solution, it self-assembled spontaneously into spherical aggregates, with an AP rod core and a shell of PEG coil, which is similar to the small aggregates in our simulation prediction.…”
Section: Effects Of Coil Length and Rod Lengthsupporting
confidence: 80%
See 2 more Smart Citations
“…Huang et al has studied a coil-rod-coil triblock copolymer of poly(ethylene glycol) (PEG) and an aniline pentamer (AP), a PEG-block-AP-block-PEG system. 21 They found that when the triblock copolymer was added directly into an aqueous solution, it self-assembled spontaneously into spherical aggregates, with an AP rod core and a shell of PEG coil, which is similar to the small aggregates in our simulation prediction.…”
Section: Effects Of Coil Length and Rod Lengthsupporting
confidence: 80%
“…[12][13][14] In contrast to classical coil blocks, the rigidity of the chain blocks results in a special molecular packing due to its liquid crystalline character, causing the copolymers to aggregate into various thermodynamically stable supramolecular structures. [15][16][17][18][19][20][21] Li et al synthesized a coil-rod-coil triblock copolymer consisting of oligo (p-phenylene-ethynylene) as the rodlike block and polystyrene as the coillike block. 19 It was shown that the segregation of these triblock copolymers in solution could be controlled by manipulating the solvent composition, thus demonstrating a unique solvatochromatic behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As alternative polymers for intractable polyaniline, oligoaniline-containing polymers (OCPs) feature enhanced solubility, processability and tunability, while retain much of polyaniline's functional capabilities. Consequently, several of OCPs including polyamides, polyimides, polyureas, poly(aryl ether)s, and polyolefins have been designed and prepared through various synthetic strategies [11][12][13][14][15][16][17][18][19][20], such as direct polymerization of oligoaniline-functionalized monomers, and post-functionalization of polymers using oligoanilines. These synthesized OCPs with different topological structures, such as alternating, blocked, grafted, hyperbranched and networked have been applied to fabricate electrochromic devices, anticorrosive coatings, sensors, and tissue engineering materials [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, many new strategies have been explored and applied to synthesize polyaniline derivatives with improved solubility and processability. An alternative strategy is the synthesis of oligoaniline‐containing polymers, which feature superior solubility, processability and tunability, while retaining much of polyaniline's functional capabilities . Two tactics are commonly employed to synthesize oligoaniline‐containing polymers: direct polymerization of oligoaniline‐functionalized monomers, and postfunctionalization of polymers using oligoaniline groups.…”
Section: Introductionmentioning
confidence: 99%